Evaluation of cutting parameters on heat-affected zone in wood plastic composites by pulsed fiber laser - Mohd Khairul Domadi,; Mohd Idris Shah Ismail,; Mohd Zuhri Mohamed Yusoff,; Hanif Mohd Pisal, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Biodegradable and environmentally friendly composite materials such as wood plastic composites (WPCs) have gained attention in industrial applications due to environmental concerns and global sustainability goals. However, owing to their unique structures and properties, cutting on WPCs can be challenging. Continuous wave (CW) mode laser may result in heat build-up and easily warp the WPCs during laser cutting. Therefore, minimizing these defects and determining the cutting parameters that influence the heat-affected zone (HAZ) by pulsed mode laser is essential. In this present work, 1 mm thickness of WPC 30 wt.% of wood fiber (WF) filled with recycled high-density polyethylene (rHDPE) has been experimentally cut by single-mode pulsed fiber laser to evaluate the minimum laser energy required to cut the WPC and the influence of cutting parameters on the HAZ. The HAZ was measured using a digital microscope, and the statistical significance of the cutting parameters to HAZ was determined by analysis of variance (ANOVA). The results confirmed that a minimum linear energy of more than 9 J/mm is required to cut the WPC. It has been found that the cutting speed is the major influence on the HAZ, followed by pulse width. Adequate interaction time by cutting speed and duration of the single-laser pulse also significantly affects the cutting process. The higher gas pressure could minimize the HAZ at the surrounding cutting region of the WPCs. Understanding the influence of these parameters could minimize the thermal effect of HAZ and improve the laser cut quality.